1991
DOI: 10.1097/00000658-199108000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intraoperative Hypotension and Perioperative Blood Transfusion on Disease-free Survival in Patients with Complete Resection of Golorectal Liver Metastases

Abstract: An increased interest in surgical treatment of liver metastases from colorectal origin has evolved recently. However not all patients benefit from this approach, with early recurrence and death still being encountered. To evaluate clinical as well as perioperative factors that might significantly affect the outcome of patients with completely resected colorectal liver metastases, we examined 116 patients who underwent resection between September 1987 and August 1989. Median follow-up time was 13.2 months (0.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
13

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(81 citation statements)
references
References 22 publications
4
64
0
13
Order By: Relevance
“…Currently, it is universally accepted that liver resection is associated with the highest survival rates (3,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Even in the present study the 10-year OS rate was 17.1%, similar to those already reported in the literature (10,14).…”
Section: Discussion Discussionsupporting
confidence: 86%
“…Currently, it is universally accepted that liver resection is associated with the highest survival rates (3,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Even in the present study the 10-year OS rate was 17.1%, similar to those already reported in the literature (10,14).…”
Section: Discussion Discussionsupporting
confidence: 86%
“…Apesar dos dados controversos e conflitantes em relação a esse fator prognóstico e a todos os outros, há consenso na literatura (3,12,23,26,29,33,36,39,41,45) : não há contra-indicação para a ressecção de metástase com tamanho maior do que 5 cm.…”
Section: Discussionunclassified
“…Resultados diferentes foram relatados por JAECK et al (22) , CADY et al (8) e AMBIRU et al (3) , que não consideraram o intervalo de tempo entre a ressecção do tumor primário e o surgimento da metástase hepática como fatores prognósticos independentes. Apesar dos resultados discordantes a respeito da importância desse fator, há consenso na literatura (3,12,23,26,28,29,36,39,41,45) de que o intervalo entre a ressecção do tumor primário e o surgimento da metástase no fígado não contra-indica a ressecção hepática.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate. Several investigators regard three tumours as an upper limit when liver resection is to be performed (61,62,64,66), while in other studies the tumour number has not been found to be a significant prognostic factor (59,60,63,65,67). It is estimated that 10 Á/20% of all patients with colorectal liver metastases are candidates for liver surgery (76).…”
Section: Resection Of Recurrencementioning
confidence: 99%